Digital Eye Strain in the Screen Era: Can Blue-Light Filtering Lenses Make a Difference? - Mirkovic, Andrea; Savić , Nikola (Halo 194 Scientific Journal of Emergency Medicine, 2026)
Increased exposure to digital screens in modern lifestyles has contributed to a rising prevalence of digital eye strain (DES), characterized by ocular discomfort, dryness, blurred vision, and headaches. Blue light–filtering spectacle lenses have been proposed as a non-invasive strategy to alleviate these symptoms; however, current evidence regarding their clinical effectiveness remains inconsistent.This randomized controlled study evaluated the short-term effects of selectively designed and commercially available blue light–filtering lenses on subjective digital eye strain in healthy adults. A total of 53 participants were randomly assigned to three groups: Selective blue-light filtering lenses group , Commercial blue-light filtering lenses group, or standard lenses without blue light filtration. Participants used the assigned lenses during routine digital screen exposure over a 14-day period.Subjective outcomes were assessed using the Digital Eye Strain Questionnaire (DES-Q). All participants completed the study without adverse events. Both intervention groups demonstrated greater reductions in DES-Q scores compared with the control group (sBLF 45%; BLF 40%; control: 10%; p < 0.05). However, no statistically significant differences were observed between the two blue light–filtering lens groups.These findings suggest that blue light–filtering lenses may be associated with a reduction in subjective symptoms of digital eye strain in the short term. Nevertheless, given the subjective nature of outcomes and the short follow-up period, results should be interpreted with caution.